Determination of some biochemical parameters in clinically healthy and anemic dromedary camels: Al-Dhalimy A.M. and Al-Hadithy H. AH. - AH., Al-Hadithy H. (The Iraqi Journal of Veterinary Medicine, 2017)
The study was conducted on 150 healthy and 102 diagnosed iron deficient anemic camels to determine serum iron, total iron binding capacity, unbound iron binding capacity, transferrin saturation, copper and cobalt concentrations. The normal (81 males and 69 females) and anemic (48 males and 54 females) groups both aged between 1-15 years in Najaf governorate- Iraq. Blood samples were collected from the jugular veins into plain tubes during the period November 2014 until May 2015, and the separated sera were used for the measurement of studied parameters. Results showed that the ranges and means ± SE in normal and anemic camels were as follows; Serum iron concentration was 7.37-19.48 μmol/L and 12±0.22 μmol/L, 1.52-15.70 μmol/L and 8.43±0.21 μmol/L, respectively, TIBC 73.80-108.47 μmol/L and 89.19±0.7 μmol/L, 93.12-135.32 μmol/L and 111.28±1.02 μmol/L, respectively, UIBC 57.5-95.25 μmol/L and 76.5±0.74 μmol/L, 83.27-125.69 μmol/L and 102±1.06 μmol/L, respectively, TS% 7.80- 24.04 % and 14.3 ±0.27%, 1.22-14.79% and 7.6±0.21%, respectively, serum copper 6.28-16.5 μmol/L and 11±0.2 μmol/L, 3.67-12.40 μmol/L and 7±0.19 μmol/L, respectively and serum cobalt 0.84-6.78 μmol/L and 3±0.13 μmol/L, 0.42-6.42 μmol/L and 2.67±0.16 μmol/L, respectively. However, There was a significant (P<0.05) decrease in serum iron, TS% and copper. While, there was a significant (P<0.05) increase in serum TIBC and UIBC of anemic camels in comparison with normal control. The cobalt concentrations were almost similar in both groups. The present data recorded reference ranges and mean values of specific biochemical parameters in clinically normal and anemic camels with significant differences between them.